A tecnologia como recurso no ensino e aprendizagem de música para deficientes visuais. - Silva, Joelson Belarmino da (2024)
This work's main objective is to analyze historical and sociocultural aspects of teaching and learning for people with visual impairment, outlining an overview of issues of social inclusion, public policy actions and private initiative, and relating them to reflections on the topic, where authors will be presented, whose works and publications range from scientific methods to practical/experimental or empirical methods, which aim to contribute to the social inclusion of visually impaired people by promoting equality and equity through technological resources and professional training. It also covers the importance of public policies and private initiative and analyzes the current scenario of musical education for people with visual impairments.